Motivasi Beriman Katolik Bagi Katekumen Di Paroki Katedral Santa Maria Palangka Raya - Kara Agustri; Silvester Adinuhgra; Paulina Maria Ekasari Wahyuningrum (Sepakat : Jurnal Pastoral Kateketik, 2023)
This study aims to describe the motivations of the Catholic faithful for catechumens at the Santa Maria Cathedral Parish of Palangka Raya. This research is based on the researcher's interest in the reality that the catechumens of the Palangka Raya cathedral parish come from various religions. This fact inspired researchers to find out more deeply what motivated them to become Catholics. This research uses a qualitative approach with descriptive methods. This research was conducted on May 25 – June 10, 2023. The research data was obtained using the interview method which was carried out together with 8 catechumens, 1 priest, 3 catechists or accompanying pastoral officers for catechumens. The data obtained was analyzed using the "Miles and Hubberman" analysis method, which was divided into three stages, namely reduction, data presentation, and drawing conclusions. Based on the results of the research, it can be interpreted that the motivation of the Catholic faithful for the Catechumens at the Santa Maria Cathedral Parish in Palangka Raya really comes from a sincere intention because they experience various experiences of the Christian faith that are truly real in their lives. So, they became Catholics not out of compulsion, so that even though they experienced various challenges during the catechumenate process, they remained strong and convinced of their vocation to become Catholics.